A case study of transformational leadership communicative strategies of Wolfgang Pfuner of Apo View Hotel - Hinalao, Valerie Lisha Marie V.
Transformational leadership and its role in organizational change is one of the most important aspects in studying organizational communication. In the context of intercultural transformational leadership, a different set of organizational values exists, driven by the cultural differences of the leaders and the members. In studying the dynamics of an organization with a touch of intercultural communication, it is very important to note the kind of strategies that leaders use to effectively communicate to an organization of a different culture. In this study, A Case of Transformational Leadership: Communicative Strategies of Wolfgang Pfuner of Apo View Hotel Davao, the researcher dug deeper into the communicative strategies were gauged according to two viewpoints: Pfuner's perspective as a leader and Mr. Prisco Baluca's as an employee of the organization. Pfuner, as the resident manager, came up with a vision that helped the organization move to a better status. In transforming the organization, Pfuner had to make use of his own knowledge of hotel management, which he was able to learn in Europe. Pfuner injected his own idea of hotel management, making sure that it will be effective for the Filipino workplace. Baluca's perspective embodied a confirmation and a complement to Pfuner's perception of doing work. It is important to consider the differences in understanding and knowledge between the foreign culture and the host culture. In this study, the researcher was able to define the role of communication and intercultural competence in the context of Apo View's organizational behavior and values. It is important to note that leadership strategies in intercultural contexts rely so much on the leader's intercultural competence and his ability to make use of his own foreign culture and dealing with the local culture, in crafting policies for the organization and help it move forward.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication